2012
DOI: 10.1088/0004-637x/746/2/119
|View full text |Cite|
|
Sign up to set email alerts
|

Three-Minute Oscillations Above Sunspot Umbra Observed With the Solar Dynamics Observatory/Atmospheric Imaging Assembly and Nobeyama Radioheliograph

Abstract: Three-minute oscillations over a sunspot's umbra in AR 11131 were observed simultaneously in UV/EUV emission by the Solar Dynamics Observatory (SDO)/Atmospheric Imaging Assembly (AIA) and in radio emission by the Nobeyama Radioheliograph (NoRH). We use 24 hr series of SDO and 8 hr series of NoRH observations to study spectral, spatial, and temporal variations of pulsations in the 5–9 mHz frequency range at different layers of the solar atmosphere. High spatial and temporal resolution of SDO/AIA in combination … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
61
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 33 publications
9
61
0
Order By: Relevance
“…An exception is the power around 5.5mHz in the Ca II K, Hα, and IRIS2796 Å channels, where the power/distance behavior appears to be reversed, i.e., the power near the umbral center is higher than that at the outer radii. This is perhaps similar to the findings of Reznikova et al (2012), where the authors show that oscillations with relatively higher frequencies are more pronounced near the umbral center than at the peripheral regions. Raja Bayanna et al (2014) reported similar observations suggesting larger power at high frequencies in a sunspot umbra compared to that at the umbra-penumbra boundary at chromospheric heights.…”
Section: Radial Variationsupporting
confidence: 89%
“…An exception is the power around 5.5mHz in the Ca II K, Hα, and IRIS2796 Å channels, where the power/distance behavior appears to be reversed, i.e., the power near the umbral center is higher than that at the outer radii. This is perhaps similar to the findings of Reznikova et al (2012), where the authors show that oscillations with relatively higher frequencies are more pronounced near the umbral center than at the peripheral regions. Raja Bayanna et al (2014) reported similar observations suggesting larger power at high frequencies in a sunspot umbra compared to that at the umbra-penumbra boundary at chromospheric heights.…”
Section: Radial Variationsupporting
confidence: 89%
“…For investigating statistical properties of the intensity variations in different channels, we selected two square regions of interest (ROI 1 and 2) shown in Φ = −3.98 • ). This sunspot showed well pronounced 3-min oscillations which were previously detected with SDO/AIA (Reznikova et al 2012;Yuan et al 2014;Deres & Anfinogentov 2015).…”
Section: Noise-testing Of Sdo/aia Datasupporting
confidence: 75%
“…In particular, the analysed sunspot showed clear 3-min oscillations A153, page 8 of 9 of a non-regular deep-modulated wave-train profile shape (see, e.g., Fig. 4 in Reznikova et al 2012). Due to its adaptive nature, EMD was chosen as the most suitable method for processing such sort of signals.…”
Section: Discussionmentioning
confidence: 96%
“…Thomas et al (1987) observed multiple peaks in the threeminute band (4.5-10 mHz) from both space and ground instruments. A similar excited range of frequencies is present in Reznikova et al (2012). A recent overview of magnetohydrodynamic waves and coronal seismology can be found in De Moortel & Nakariakov (2012).…”
Section: Introductionmentioning
confidence: 56%
“…Furthermore, many observations show a harmonic wave structure (Yuan et al 2011;Reznikova et al 2012;Sych et al 2011) as opposed to the saw-tooth signal required for the shock wave model. As such, the chromospheric resonator model is a promising explanation for the three-minute oscillations.…”
Section: Introductionmentioning
confidence: 99%